The Constitutional Legitimacy of Temporary Advocate Identification in the Indonesian Legal System - Lutfiadi, Lutfiadi; Wardani, Win Yuli; Heryanti, Febrina; Camelia, Noer Dini; Hanayanti, Citra Siwi (Jurnal Ilmu Hukum Kyadiren, 2025)
The rejection of the Temporary Advocate Identification (TPSA) by judicial panels in court proceedings presents significant legal and constitutional concerns, particularly with respect to the principles of legal certainty and the client’s right to legal representation. This study seeks to examine the legal status of the TPSA based on Indonesia’s positive legal framework, especially in relation to Law No. 18 of 2003 on Advocates and its implementing regulations. Furthermore, it evaluates the authority of advocate organizations in issuing identification cards as a means of establishing professional legitimacy. Utilizing a normative legal method combined with case study analysis of selected judicial decisions, this research finds that although TPSA is not explicitly regulated in statutory provisions, it possesses a valid administrative foundation. The rejection of TPSA in court proceedings has adverse implications for the constitutional rights of advocates and impairs clients’ access to legal counsel. Accordingly, the study recommends the establishment of formal regulatory recognition of TPSA to promote legal equality, procedural consistency, and the effective exercise of the right to defense within the judicial system.